Rearing temperature induces changes in muscle growth and gene expression in juvenile pacu (Piaractus mesopotamicus) - Paula, Tassiana Gutierrez de [UNESP]; Alves de Almeida, Fernanda Losi; Carani, Fernanda Regina [UNESP]; Vechetti-Junior, Ivan Jose [UNESP]; Padovani, Carlos Roberto [UNESP]; Simoes Salomao, Rondinelle Arthur [UNESP]; Mareco, Edson Assuncao [UNESP]; Santos, Vander Bruno dos; Dal-Pai-Silva, Maeli [UNESP] (Elsevier B.V., 2014)
Pacu (Piaractus mesopotamicus) is a fast-growing fish that is extensively used in Brazilian aquaculture programs and shows a wide range of thermal tolerance. Because temperature is an environmental factor that influences the growth rate of fish and is directly related to muscle plasticity and growth, we hypothesized that different rearing temperatures in juvenile pacu, which exhibits intense muscle growth by hyperplasia, can potentially alter the muscle growth patterns of this species. The aim of this study was to analyze the muscle growth characteristics together with the expression of the myogenic regulatory factors MyoD and myogenin and the growth factor myostatin in juvenile pacu that were submitted to different rearing temperatures. Juvenile fish (1.5 g weight) were distributed in tanks containing water and maintained at 24 degrees C (G24), 28 degrees C (G28) and 32 degrees C (G32) (three replicates for each group) for 60 days. At days 30 and 60, the fish were anesthetized and euthanized, and muscle samples (n = 12) were collected for morphological, morphometric and gene expression analyses. At day 30, the body weight and standard length were lower for G24 than for G28 and G32. Muscle fiber frequency in the <25 mu m class was significantly higher in G24, and the >50 mu m class was lower in G24. MyoD gene expression was higher in G24 compared with that in G28 and G32, and myogenin and myostatin mRNA levels were higher in G24 than G28. At day 60, the body weight and the standard length were higher in G32 but lower in G24. The frequency distribution of the <25 pm diameter muscle fibers was higher in G24, and that of the >50 mu m class was lower in G24. MyoD mRNA levels were higher in G24 and G32, and myogenin mRNA levels were similar between G24 and G28 and between G24 and G32 but were higher in G28 compared to G32. The myostatin mRNA levels were similar between the studied temperatures. In light of our results, we conclude that low rearing temperature altered the expression of muscle growth-related genes and induced a delay in muscle growth in juvenile pacu (P. mesopotamicus). Our study provides a clear example of thermally induced phenotypic plasticity in pacu fish and shows that changing the rearing temperature during the juvenile stage can have a considerable effect on gene expression and muscle growth in this species. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Fish; Skeletal muscle; Extrinsic factor; Myogenic regulatory factors; Myostatin